Stereoselective Total Synthesis of Mangiferaelactone using D‐Mannose as a Chiral Pool. Issue 10 (October 2015) - Reddy, Basi V. Subba; Reddy, Pathuri Sivaramakrishna; Babu, Kummari Vijaya; Reddy, Bhemavarapu Phaneendra; Yadav, Jhillu Singh
Abstract A convergent total synthesis of mangiferaelactone has been accomplished in a highly stereoselective manner from readily available D‐mannose. The following methods like organocatalytic enantioselective epoxidation, ring‐closing metathesis, and Steglich esterification have been employed as key steps, which make this approach more attractive.